Stability Analysis of an Seirs Epidemic Model with Relapse, Immune and General Incidence Rates - Bernoussi, Amine; Elkhaiar, Soufiane; Jerry, Chakib (Journal of Applied Nonlinear Dynamics, 2026)
This paper has the goal to broaden the incidence rate of an SEIRS epidemic model to a wide range of monotonic, concave incidence rates and some non-monotonic or concave cases. These incidence functions could reflect media education or psychological effect or mass action. The model takes into account relapse, recovery and immunity rates but without disease-induced death one. Applying the novel geometric approach we establish the global stability of the SEIRS model. Our analytical results reveal that the basic reproduction number completely determines the global stability of equilibria. Our conclusions are applied to two special incidence functions reflecting media and mass action.